Amylin at the interface between metabolic and neurodegenerative disorders - Lutz, Thomas A.; Meyer, Urs (Frontiers in Neuroscience, 2015)
The pancreatic peptide amylin is best known for its role as a satiation hormone in the control of food intake and as the major component of islet amyloid deposits in the pancreatic islets of patients with type 2 diabetes mellitus (T2DM). Epidemiological studies have established a clear association between metabolic and neurodegenerative disorders in general, and between T2DM and Alzheimer’s disease (AD) in particular. Here, we discuss that amylin may be an important player acting at the interface between these metabolic and neurodegenerative disorders. Abnormal amylin production is a hallmark peripheral pathology both in the early (pre-diabetic) and late phases of T2DM, where hyperamylinemic (early phase) and hypoamylinemic (late phase) conditions coincide with hyper- and hypoinsulinemia, respectively. Moreover, there are notable biochemical similarities between amylin and β-amyloids (Aβ), which are both prone to amyloid plaque formation. Amylin’s propensity to form amyloid plaques is not restricted to pancreatic islet cells, but readily extends to the CNS, where it has been found to co-localize with Aβ plaques in at least a subset of AD patients. Hence, amylin may constitute a “second amyloid” in neurodegenerative disorders such as AD. We further argue that hyperamylinemic conditions may be more relevant for the early processes of amyloid formation in the CNS, whereas hypoamylinemic conditions may be more strongly associated with late stages of central amyloid pathologies. Advancing our understanding of these temporal relationships may help to establish amylin-based interventions in the treatment of AD and other neurodegenerative disorders with metabolic comorbidities.